Impact of Histologic Risk Factors on Recurrence Rates for Oral Cavity Squamous Cell Carcinoma. (July 2023) - Kligerman, Maxwell P.; Moon, Peter K.; Tusty, Mahbuba; Cloutier, Jeffrey M.; Ma, Yifei; Holsinger, Christopher F.; Divi, Vasu
Objectives: This study assesses the impact of adverse histologic risk factors including worst pattern of invasion (WPOI), predominant pattern of invasion (PPOI), tumor budding, and tumor infiltrating lymphocytes (TILS), on risk of recurrence in patients with early-stage Oral Cavity Squamous Cell Carcinoma (OCSCC). Methods: Retrospective chart review was performed at a single institution to identify patients with OCSCC who underwent surgical excision. Inclusion criteria included T1-T2 stage disease based on AJCC seventh edition guidelines, no cervical lymph node involvement, no perineural invasion (PNI), no lymphovascular invasion (LVI), no post-operative adjuvant radiation therapy, and cancer involving only the oral tongue or floor of mouth. Patients were excluded if they had positive final margins. A subset of 35 patients were selected for additional histologic review to determine WPOI, PPOI, TB, and TILS. Bivariable and multivariable cox analysis were performed to determine variables associated with recurrence. Results: One hundred and sixty-one patients met criteria and were included in the analysis. Variables that were significantly associated with recurrence on bivariable analysis included tumors with high risk PPOI (groups 4 and 5; P  = .021), TB with 10 or more buds ( P  = .021), T-stage ( P  = .001), neck dissection ( P  = .03), and depth of invasion (DOI) >4 mm ( P  = .044). Multivariable cox proportional hazards found T-stage (HR: 6.40; 95% CI 1.67, 24.50; P  = .007), neck dissection (HR: 0.23; 95% CI 0.07, 0.82; P  = .023), and TBs (HR: 1.17; 95% CI 1.05, 1.30; P  = .006) to be most predictive of recurrence. Conclusions: TB is a strong predictor of recurrence. WPOI, PPOI, and TILS were not statistically significant risk factors for recurrence.